Thoracolumbar interfascial plane block and erector spinae plane block for postoperative analgesia in patients undergoing spine surgery - Chitneni, Ahish; Hasoon, Jamal; Urits, Ivan; Viswanath, Omar; Orhurhu, Vwaire; Kaye, Alan; P. Eskander, Jonathan (Anestezjologia Intensywna Terapia, 2021)
Regional anaesthesia prior to surgical intervention plays an important role in reducing post-operative pain and limiting opioid consumption. Ultra- sound-guided interfascial plane blocks have gained popularity because they allow analgesia to be targeted to a specific anatomical region and provide effective pain control. In the United States, lumbar spine surgery is one of the most commonly performed procedures for pain relief in patients with low back and leg pain [1]. In recent years, the advent of the thoracolumbar interfascial plane block (TLIP) and the erector spinae plane block (ESPB) have been shown as effective interventions for pain control in patients undergoing lumbar spine surgery such as an hemilaminectomy. Additionally, the ESPB has even been utilized as the main anaesthetic in some cases [2].